A TRIBUTE TO PROFESSOR ZHANG CHANGSHOU 張長壽 (1929–2020). (September 2021) - Li, Feng
Abstract: Zhang Changshou was one of the most important archaeologists of modern China, and a founder of Western Zhou archaeology. Zhang is particularly well known as the author of a series of works that established the chronology of the Western Zhou material culture and is esteemed for his excellent scholarship also on bronzes and jade objects, characterized by a strong basis in field archaeology. Among his academic appointments are Director of the Feng-Hao Archaeological Team in 1963–1988, and Associate Director of the Institute of Archaeology (Chinese Academy of Social Sciences) in 1985–1988. Zhang was also a pioneer of Sino-American collaboration (with Harvard University) in field archaeology and was elected a Corresponding Member of the German Archaeological Institute in 1988. Zhang passed away in Beijing on January 30, 2020. This article summarizes his academic accomplishments.